Genesis of volunteering in Russia: historical and cultural aspects - Alexey Eduardovich Zimin (Вестник Майкопского государственного технологического университета, 2023)
In Russia volunteering has become extremely popular in the last decade. The purpose of the research is to identify the stages of the formation of volunteering, the influence of the history and culture of the country on the specifics of volunteering.Various sciences are engaged in the study of the activities of volunteer associations, for ex- ample, such as: sociology, psychology, history, etc. Representatives of different strata of society take part in volunteer communities. Despite the fact that volunteering as a phenomenon appeared relatively recently, it has acquired an important social significance. The volunteer movement has become massive in recent years.Gradually, a culture of volunteering is being formed, but, like all new phenomena, it has not yet fully developed. Nevertheless, it can be noted that volunteering is currently a socially significant area for society and the state.The article attempts to single out the main stages in the development of volunteer movement in Russia, and gives a description of each stage.